Teaching Humor in French Literature in the 21st-Century Classroom - Jennifer J. Willging (Studies in 20th & 21st Century Literature, 2026)
In this essay I reflect on the anxiety-raising process of constructing and teaching a course on humor in twentieth-century French literature in what seems like an increasingly humorless time, and university. That most faculty today reflect more than ever on diversity, inclusivity, and sensitivity when choosing course materials is certainly a positive and welcome change from an earlier time. However, some of funniest authors in French literary history have also been among the most controversial, still (or perhaps especially) today: Rabelais, Voltaire, Diderot, Flaubert, Céline, Despentes, Houellebecq, to name a few. In choosing texts for this and indeed all my literature courses, I increasingly worry about who a particular work might offend, for good literature is not a non-contact sport. It does not seek first to comfort or confirm but to challenge, contradict, provoke, and sometimes shock. Characters and narrators are not always nice, especially but not only when they are funny. This essay will treat briefly debates about certain currents in contemporary American culture and the university—for example, what critics of them have called cancel culture, safetyism, and wokism—and will ask how such debates may inform the teaching of humor in literature, as well as the use of humor when teaching literature. It contends that the goal of teaching students to detect humor in literature and to accurately analyze its devices, objectives, and targets—and more broadly, to become skilled and perceptive decipherers of the written word—is essential for their development into informed, articulate, and resilient adults and is thus worth the risk of offending.
Keywords: Teaching humor; twentieth-century French literature; cancel culture; trigger warnings; safe spaces